Introducing the maximum displacement technique for structural enhancement of rectangular and curved plates in thermoset 3D-printed concrete formwork - Zuffain Hussan; Marco Brander; Berin Šeta; Jon Spangenberg; Sebastian Andersen; Gregor Fischer (Engineering Structures, 2026)

Cognitive sequelae in post-COVID-syndrome: a Danish-Swedish case-control study - Johan Frederik Mebus Meyer Christensen; Rikke Meyer; Madlene Holmqvist; Katherine Carlson; Sebastian Palmqvist; Fredrik Kahn; Gesche Jürgens; Christian Niels Meyer; Kirsten Brændholt Rasmussen; Tanja Korfitsen Carøe; Preben Homøe; Simon Westphal Jespersen; et al. (Infectious Diseases, 2026)

Biochemistry of Arctic kelp specimens is conditioned by the local environment - Sarina Niedzwiedz; Clara Voigt; Sebastian Andersen; Nora Diehl; Raphaëlle Descôteaux; Børge Damsgård; Kai Bischof (Marine Environmental Research, 2025)

Process configurations for emission control: CESAR1 emission behavior in biomass combustion gas treatment - Maria Dimitriadi; Christina Andersen; Isaac Appelquist Løge; Randi Neerup; Søren Jensen; Jakob Lindkvist Karlsson; Pantelis Bountzis; Nomiki Kottaki; Frantz Bræstrup; Kristian Røhe Kongst Krum; Søren Christensen; Sebastian Nis Bay Villadsen; et al. (Chemical Engineering Journal, 2025)

Modelling the stochastic importation dynamics and establishment of novel pathogenic strains using a general branching processes framework - Jacob Curran-Sebastian; Frederik Mølkjær Andersen; Samir Bhatt (Mathematical Biosciences, 2025)

Fucoidans from Laminaria hyperborea demonstrate bactericidal activity against diverse bacteria - Michael L. C. Beagan; Line L Bang; Jens S. Pettersen; Rasmus B. Grønnemose; Sebastian Foertsch; Thomas E. Andersen; Ming Ding (Journal of Applied Phycology, 2024)
Fucoidans are a heterogenous class of fucose-rich sulfated carbohydrates which have attracted increasing attention in cancer and inflammation research due to their bioactive properties. There are reports that fucoidans may have direct antibacterial effects and synergy with antibiotics. However, the literature is conflicting, potentially due to the limited reporting of origin, characteristics, and extraction methods of the fucoidans tested. Here we report the results of 18 defined fucoidans screened for direct, indirect, and synergistic antibacterial effects. 15 distinct fucoidan fractions, isolated from Laminaria hyperborea using a solvent-free extraction process, were characterised for molecular weight, pH, viscosity, and sulfur content. These, together with three commercially available crude fractions, were assessed at concentrations from 0.03125-24 mg mL -1 for minimum inhibitory concentration against Staphylococcus aureus , Streptococcus mutans and Streptococcus sanguinis. Furthermore, we tested a selection of fucoidans for antibacterial synergy with vancomycin and indirect antibacterial effects in whole blood survival assays. Reverse-transcription quantitative polymerase chain reaction (RT-qPCR) was performed to assess the stress response in fucoidan-treated S. aureus cultures. We have identified one fucoidan fraction with bactericidal activity against diverse bacteria. This effect is dose-, fucoidan fraction- and bacteria-specific, and furthermore, not related to osmotic stress. No synergistic effects were observed with fucoidan in combination vancomycin. Fucoidans have exciting potential as antimicrobial agents. Further analysis is required to establish the precise molecular characteristics responsible for their potent bactericidal activity.

Single-component multi-rate real time hybrid simulation pilot test on a composite structure - Jacob P. Waldbjoern; Sebastian Andersen; Jacob Herold Hoegh; Christian Berggreen (Engineering Structures, 2024)

Solvent degradation and emissions from a CO2 capture pilot at a waste-to-energy plant - Randi Neerup; Valdemar E. Rasmussen; Sai H.B. Vinjarapu; Anders H. Larsen; Meng Shi; Christina Andersen; Karsten Fuglsang; Lars K. Gram; Jonas Nedenskov; Jannik Kappel; Peter Blinksbjerg; Søren Jensen; et al. (Journal of Environmental Chemical Engineering, 2023)

Editorial: Sustainable Development Goal 14 - Life Below Water: Towards a Sustainable Ocean - Brett W. Molony; Alex T. Ford; Ana M. M. Sequeira; Angel Borja; Anna Milena Zivian; Carol Robinson; Christian Lønborg; Elva G. Escobar-Briones; Emanuele Di Lorenzo; Jesper H. Andersen; Marius N. Müller; Michelle J. Devlin; et al. (Frontiers in Marine Science, 2022)

Work limitations due to neck-shoulder pain and physical work demands in older workers: cross-sectional study - Mohammad Bayattork; Sebastian Venge Skovlund; Emil Sundstrup; Lars Louis Andersen (International Archives of Occupational and Environmental Health, 2021)

Estimation of Spinal Loading During Manual Materials Handling Using Inertial Motion Capture - Frederik Greve Larsen; Frederik Petri Svenningsen; Michael Skipper Andersen; Mark de Zee; Sebastian Skals (Annals of Biomedical Engineering, 2020)

Electromyographic evaluation of high-intensity elastic resistance exercises for lower extremity muscles during bed rest - Jonas Vinstrup; Sebastian Skals; Joaquin Calatayud; Markus Due Jakobsen; Emil Sundstrup; Matheus Daros Pinto; Mikel Izquierdo; Yuling Wang; Mette K. Zebis; Lars Louis Andersen (European Journal of Applied Physiology, 2017)